Pengaruh Kualitas Pelayanan dan Kepercayaan Terhadap Loyalitas Pelanggan Pada Mitra Ninja Xpress Sukamanah Kota Tasikmalaya - Siti Yumna Nabilla Qatrunnada; Cecep Hermana (Jurnal Ilmiah Wahana Pendidikan, 2023)
Loyalty is a measure of a customer's relationship to a product or service. This measure is able to describe whether or not a customer may switch to another brand. Customer loyalty can also be affected by Quality of Service and Trust. Good service quality if accompanied by trust is expected to increase customer loyalty to Mitra Ninja Xpress Sukamanah Kota Tasikmalaya. This research was conducted using descriptive and verifiable methods. The sample used was a simple random sampling method with a total sample of 305 respondents from a population of 1,271. The partial effect of service quality on customer loyalty was 0.227 or 22.7% and the partial effect of trust on customer loyalty was 0.568 or 56.8%. This shows a significant partial influence between quality of service and trust on customer loyalty. Service quality and trust have a significant influence, both partially and simultaneously on Customer Loyalty. The total effect of service quality and trust on customer loyalty was 0.452 or 45.2% and the remaining was 0.548 or 54.8% the influence of other variables not studied in this study.